Patterns of Obesity and Lymph Fluid Level during the First Year of Breast Cancer Treatment: A Prospective Study - Fu, Mei R. (J Pers Med, 2015)
Obesity is one of the risk factors for developing lymphedema following breast cancer treatment. We prospectively enrolled 140 women and followed the participants for 12 months after surgery to investigate patterns of obesity and lymph fluid level in the first year of cancer treatment. Electrical bioimpedance devices were used to measure weight, BMI, and percent of body fat as well as lymph fluid level. General instructions were given to the participants on maintaining pre-surgery weight. Among the 140 participants, 136 completed the study with 2.9% attrition. More than 60% of the participants were obese (30.8%) or overweight (32.4%), while only two participants were underweight and about 35% had normal weight. This pattern of obesity and overweight was consistent at 4–8 weeks and 12 months post-surgery. At 12 months post-surgery, the majority of the women (72.1%) maintained pre-surgery weight and 15.4% had >5% weight loss; 12.5% of the women increase >5% of their weight. Significantly more patients in the obesity group had lymphedema defined by L-Dex ratio >7.1 than those in the normal/underweight and overweight group at pre-surgery and 4–8 weeks post-surgery. There was a trend of more patients in the obesity group had L-Dex ratio >7.1 at 12 months post-surgery. Obesity and overweight remain among women at the time of cancer diagnosis and the patterns of obesity and overweight continue during the first year of treatment. General instructions on having nutrition-balanced and portion-appropriate diet and physical activities daily or weekly can be effective to maintain pre-surgery weight.